2007
DOI: 10.1002/jsfa.2871
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of diets containing graded levels of wheat distillers grains with solubles fed to broiler chicks

Abstract: This feeding trial was conducted to determine the effects of graded levels of wheat distillers dried grains with solubles (DDGS) on nutrient digestibility and performance when fed to broiler chicks. A total of 125, day-old, male broiler chicks (52.8 ± 0.6 g) were fed wheat/soybean meal-based diets containing 0, 5, 10, 15 or 20% wheat DDGS. There were five birds per pen and five replicate pens per treatment. Digestibility coefficients for dry matter (P = 0.001), energy (P = 0.001) and phosphorus (P = 0.001) dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 12 publications
5
34
3
2
Order By: Relevance
“…This value is somewhat lower than that reported by Boila and Ingalls (1994a); average 40.793.1%) for wheat-based DDGS, but similar to that (35.7%) reported by Thacker and Widyaratne (2007). Spiehs et al (2002) reported 30.29 6.4% CP for corn-based DDGS, while Kleinschmit et al (2007) reported an average CP value of 32.1%.…”
Section: Resultssupporting
confidence: 61%
“…This value is somewhat lower than that reported by Boila and Ingalls (1994a); average 40.793.1%) for wheat-based DDGS, but similar to that (35.7%) reported by Thacker and Widyaratne (2007). Spiehs et al (2002) reported 30.29 6.4% CP for corn-based DDGS, while Kleinschmit et al (2007) reported an average CP value of 32.1%.…”
Section: Resultssupporting
confidence: 61%
“…The chickens administered the mixtures with 10 % addition of DDGS, were characterised by deteriorated body weight gains and feed conversion ratio. Thacker & Widyaratne (2007) applied feed mixtures with different levels of wheat DDGS (0, 5, 10, 15 and 20 %) in chicken feeding. They showed that DDGS addition to feed (15 %) did not affect the production results.…”
Section: Discussionmentioning
confidence: 99%
“…These products are constituted by components from initial raw material, being insensitive to fermentation (non-starch carbohydrates, protein, fat, ash and others), and biomass of the multiplied yeasts. Dried grains of cereal distillers are rich in protein, exogenous amino acids, B-group vitamins, biotin and mineral compounds, including phosphorus (Koreleski & Świątkiewicz 2006, Thacker & Widyaratne 2007, Min et al 2008. The process of yeast fermentation results in the synthesis of microbiological phytase and, therefore, the availability of phosphorus in the discussed products is considerably greater than in other vegetal feeds (Martinez Amezcua et al 2004, Lumpkins & Batal 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…따라서 최근의 연구들은 다양한 축종에 대하여 사료용 옥수 수를 대체하기 위한 연구 (Mateoes et al, 2006(Mateoes et al, , 2007Nyannor et al, 2007;Donkin et al, 2009;Archimede et al, 2010) 와 더불어 바이오 에너지 생산에 따른 그 부산물로서, 대량 생산되는 옥수수 주정박(Corn Distiller's Dries Grains with Solubles, CDDGS)의 사료자원으로서 이용가치 증진 향상을 위한 많은 연구가 지속되어 왔다 (Waldroup et al, 1981;Parsons et al, 1983;Lumpskin et al, 2003Lumpskin et al, , 2004Thacker and Widyaratne, 2007).…”
unclassified